Edukasi Perlindungan Mata terhadap Paparan Sinar Ultraviolet pada Pekerja PPSU: Upaya Peningkatan Kesadaran Kesehatan Mata - Denni Boy Saragih; Desi Hartati Silaen (FKIP, Universitas Palangka Raya, 2026)
Ultraviolet (UV) exposure is a significant ocular health risk for outdoor workers, particularly PPSU officers in tropical regions. This community engagement sontoto program aimed to improve UV risk awareness and eye protection. Methods included basic eye examinations, interactive education, and counseling on personal protective equipment involving 53 PPSU workers in Pengadegan, South Jakarta. Results indicated that participants initially had limited knowledge and inconsistent use of eye protection. Following the intervention, there was a notable increase in understanding and a willingness to adopt preventive behaviors. In conclusion, simple educational interventions effectively enhance eye health awareness among urban outdoor workers. Such programs should be sustained as part of occupational health promotion and prevention strategies to ensure long-term worker safety.